RELATIONAL DIALECTICS ON SUNDANESSE-ARABIAN MARRIAGE - Ganiem, Leila Mona (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2009)
In a heterogenic   country.   such  as Indonesia,   an  intercultural   marriageis  always  possible.   Many  data  reveal   that  intercultural   marriages  potentially are   more   troubled   than   marriages   of  the  same   culture.    Leslie  Baxter   and Montgomery   s  theory  ( 1998)  on relational   dialectics  analyzed   the strains   that are  conjoined    in  a  romantic   relationship.   ·        Those  are   internal  and   external·    dialectics.    In this  research   the relational   dialectics   theory   was studied   in thecultural  context  marriages  between  the Sundanese  and Arabs.  The aim  of the research    was   to:   1)   get   the  knowledge    about   internal-external     relational dialectics     of   intercultural    couples,     2)   get   the   understanding     about       the experiences   of the couples  in connect ion  to intercultural   dialectics  and  3) get the  understanding    on  how  those  couples   overcome  the  intercultural   dialectics they  face    in  their  marriage   on  the  internal   and  external   scope.    From   this research   it can be concluded  that internal  and external  dialectics  are  tended  to be  sourced    by  cultural   difference   of  each  couple.      The  most  conspicuous dialectics    of  those  couples   were  caused   by  the  individuals·    competence    or incompetence    to  predict    their  spouses    culture   or  surroundings.